The Effect of a Pocketbook On Increasing Mother Knowledge Regarding Development And Stimulation of Children 0-24 Months - Diana Hartaty Angraini; Elly Dwi Wahyuni; Aticeh Aticeh; Riyani Hasan (Jurnal Kesehatan Prima, 2020)
Failure to invest in early childhood development can cause developmental delays and stunt growth, optimal performance, and performance of children throughout their lives. Through knowledge, parents can help these children achieve the required potential to invest in early childhood development and develop physically cognitive, emotional, and social capacity. One solution to improve Parental knowledge is to provide health education through pocketbook media. This study is to determine the effect of giving pocketbooks of mother's knowledge of the development and stimulation of children  0-24 months at Posyandu, Klender Jakarta Timur. The method of this study is a quantitative research design with Quasi Experiment Non-Equivalent Design Control Group. Sampling with consecutive sampling technique. Total respondents were 58 mothers who have children 0-24 months. This research using the primary data collection method using a questionnaire. On Statistical calculations, Wilcoxon test results showed an increase in significant knowledge, between before and after treating the group intervention (p = 0,000) while the Mann Whitney test shows a difference significant between the control and intervention groups (p = 0,000).Based on the results It concluded that the pocketbook had a significant effect on improving the mother's knowledge of the development and stimulation of children 0-24 months.